The fate of endocrine disrupting chemicals during activated sludge treatment - Bagnall, John Peter (Cranfield University, 2010)
A significant route for Endocrine disrupting chemicals (EDCs) such as natural and synthetic estrogens and nonylphenolics to enter the environment is via sewage treatment. Nanogram per litre levels of these compounds have been demonstrated to cause feminisation of aquatic organisms. The utilisation of treatments such as advanced oxidation and activated carbon could remove these compounds from effluent; however these technologies are expensive and energy intensive. Determining which operating parameters control the biodegradation of EDCs during activated sludge treatment, removal could be more sustainable. This study investigates which process parameters are responsible for controlling biodegradation of estrogens and nonylphenolics during activated sludge treatment. The role ammonia oxidising bacteria upon the breakdown of estrogens was also investigated. Field-based sampling campaigns were undertaken at three activated sludge plants and pilot-scale porous pot bioreactors were utilised to further examine the individual influences of loading, hydraulic retention time (HRT) and sludge retention time (SRT) upon EDC biodegradation. Cont/d.